2006
DOI: 10.1111/j.1532-950x.2006.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell Growth Characteristics and Differentiation Frequency of Adherent Equine Bone Marrow–Derived Mesenchymal Stromal Cells: Adipogenic and Osteogenic Capacity

Abstract: The results have direct relevance to the use of BM as a potential source of adult stem cells for tissue engineering applications in equine veterinary medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
187
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(206 citation statements)
references
References 49 publications
14
187
2
3
Order By: Relevance
“…The cell population with the fusiform appearance described here in samples from both adipose tissue and bone marrow were morphologically similar to mesenchymal stem cells from human (Zuk et al 2001, You et al 2009), sheep (Fadel et al 2011), horse (Fortier et al 1998, Smith et al 2003, Hegewald et al 2004, Vidal et al 2006, 2007, Maia et. al 2012, De Vita et al 2013, and other animals reported in many studies, in which these cells were described as star-shaped or fibroblast-like.…”
Section: Discussionmentioning
confidence: 77%
“…The cell population with the fusiform appearance described here in samples from both adipose tissue and bone marrow were morphologically similar to mesenchymal stem cells from human (Zuk et al 2001, You et al 2009), sheep (Fadel et al 2011), horse (Fortier et al 1998, Smith et al 2003, Hegewald et al 2004, Vidal et al 2006, 2007, Maia et. al 2012, De Vita et al 2013, and other animals reported in many studies, in which these cells were described as star-shaped or fibroblast-like.…”
Section: Discussionmentioning
confidence: 77%
“…The isolation procedure for MSCs continues to be based on their plastic adherence properties [7,[25][26][27][28]. In addition, the nomenclature used to distinguish between isolated cells types is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The most characterized sources of MSCs are bone marrow (Fortier et al 1998, Ringe et al 2002, Mitchell et al 2003, Smith et al 2003, Kern et al 2006, Vidal et al 2006, Arnhold et al 2007, Vidal et al 2008) and the adipose tissue (Kern et al 2006, Vidal et al 2008; however, the procedures employed to isolate these tissues are still invasive and cells are usually obtained with low efficiency. Furthermore, their differentiative and proliferative potential has been reported to decrease with the age of the donor (Pittenger et al 1999).…”
Section: Introductionmentioning
confidence: 99%